Psychosocial and personal factors on identification of gifted and talented students in Owerri municipal, Imo State, Nigeria (2022)
The study investigated on psychosocial and personal factors as correlates of identification of gifted and talented students in Owerri Municipal, Imo State. The study adopted a descriptive survey research design of correlational type. The population of the study was 2,893 with a sample size 155 teachers in secondary schools in Owerri, Imo State, selected through simple random sampling techniques representing 5% of the total population. The data were collected using Teacher-student relationship Rating Scale, Teachers' self-efficacy Rating Scale and Teachers' knowledge Rating Scale. The instruments were subjected to a reliability test using Spearman Brown Rank Order which yielded a correlation coefficient of r=0.76, 0.71 and 0.83 respectively. Data collected were analyzed using the inferential statistics of Person Product Moment Correlation (PPMC) and Multiple Regression and at 0.05 alpha level of significance. The findings revealed a significant relationship between teacher-student relationship (r=.510, p(.000)<.05), teachers' self-efficacy (r=.509, p(.000)<.05), and teachers' knowledge (r=.217, p(.007)<.05) respectively and identification of gifted and talented students. The relationship of the three independent variables (teachers' self-efficacy, teacher-student relationship, teachers' knowledge) to the prediction of the dependent variable that is, identification of gifted and talented students showed a coefficient of multiple correlation R=.554 and a multiple R2of .307. Finally, the result revealed a relative contribution of the three independent variables to the dependent variable, expressed as beta weights, viz: Teachers' self- efficacy (6=307, p<.05), teacher-student relationship (6=.288, p<.05), and teachers' knowledge (6=.019, p>.05). Based on these findings, it is recommended that teacher-student relationship must always be cordial in every school since it has been established that it enhances the identification of gifted and talented students in schools.